The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1001/jamaoncol.2015.2690
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Actionability of Multigene Panel Testing for Hereditary Breast and Ovarian Cancer Risk Assessment

Abstract: In a clinically representative cohort, multigene panel testing for HBOC risk assessment yielded findings likely to change clinical management for substantially more patients than does BRCA1/2 testing alone. Multigene testing in this setting is likely to alter near-term cancer risk assessment and management recommendations for mutation-affected individuals across a broad spectrum of cancer predisposition genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
215
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 292 publications
(232 citation statements)
references
References 32 publications
10
215
3
3
Order By: Relevance
“…In this series, our aim was to answer this question, since it represents a central challenge for the future deployment of genomic medicine [25,27,[35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series, our aim was to answer this question, since it represents a central challenge for the future deployment of genomic medicine [25,27,[35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In the last 2 years, the literature assessing the contribution of multigene panel testing in cohorts of patients with HBOC has grown. The results have been consistent even though the inclusion criteria sometimes differ [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The next challenge is to determine the consequences of these results on clinical management [NCCN clinical practice Guidelines-see URL].…”
Section: Introductionmentioning
confidence: 89%
“…However, with the current popularization of gene panel assays, more data about the prevalence of those variants among women with a suspected hereditary predisposition for breast cancer have become available. In a recent prospective study of 1046 patients who were BRCA1-or BRCA2-negative and at high risk for hereditary breast or ovarian cancer, 3.8% (n = 40) were found to harbour an alternative pathogenic gene variant 24 . After CHEK2, ATM was the second most frequent variant identified, and it accounted for more than 25% (n = 11) of identifications 24 .…”
Section: Pathophysiology and Clinical Presentationmentioning
confidence: 99%
“…In a recent prospective study of 1046 patients who were BRCA1-or BRCA2-negative and at high risk for hereditary breast or ovarian cancer, 3.8% (n = 40) were found to harbour an alternative pathogenic gene variant 24 . After CHEK2, ATM was the second most frequent variant identified, and it accounted for more than 25% (n = 11) of identifications 24 . In the largest gene panel study to date, the prevalence of pathogenic ATM variants in 35,409 women with a first diagnosis of breast cancer was approximately 0.9% 25 .…”
Section: Pathophysiology and Clinical Presentationmentioning
confidence: 99%
“…Therefore proper assessment of VUS has become a major issue in clinical genetic testing. Furthermore, previous studies have demonstrated that BRCA1/2 mutation-negative patients harbored deleterious mutations in moderate-risk cancer genes such as CHEK2, ATM, and PALB2 and MMR (19,20). Despite an increasing number of HBC testing facilities, there is little information available regarding attitudes towards precision medicine for HBC in Japan.…”
Section: Introductionmentioning
confidence: 99%